Careless Reef part 4: Marsa Abu Galawa - Holthuis, Gerard (The Netherlands, 2004)
A breathtaking mash up of shape and color, where the captivating underwater images collide with each other, etching a new, accidental ecosystem. Featuring the rapturous music of Abdel Basset Hamouda, the film will mesmerize and amaze, while managing to evoke the type of primordial feelings of peace and distress only the ocean can produce.
Verzio Film Festival Submission
Keywords: Experimental films